An extensive review of experimental ochratoxicosis in poultry: II. Hemato-biochemical and immunological alterations along with other health issues. (3rd July 2021) - Khatoon, Aisha; ul Abidin, Zain
Abstract: Ochratoxins, primarily produced by certain species of Aspergillus and Penicillium are considered to be important threats for the health of poultry chicks. These fungal species are present as storage fungi within the stored feed ingredients and when they get proper growth requirements like aerobic condition coupled with high moisture contents lead to the production of ochratoxins as their secondary metabolites. In this second review of the series "An extensive review of experimental ochratoxicosis in poultry" OTA associated alterations in hematological, serum biochemical and immunological parameters have been addressed along with certain other important health issues associated with it in poultry.